The Influence of Principal Leadership Style on the Effectiveness of Islamic Education Management - Sari, Wulan (CV. Tripe Konsultan, 2024)
The purpose of this study is to ascertain how the leadership style of the principal affects the efficiency of Islamic education management at Jati Agung 2nd State Junior High School. This study employs a quantitative methodology with a correlational design, gathering data via a Likert scale questionnaire bolstered by documentation and interviews. Using a saturation sample strategy, 40 teachers and other education professionals made up the study population. The validity and reliability of the study tool were evaluated, yielding Cronbach's Alpha values of 0.82 for management effectiveness and 0.79 for leadership style. With a regression coefficient value of 0.694 and a determination coefficient (R2) of 0.482, the findings of a straightforward linear regression study demonstrate that the leadership style of the principal significantly and favorably affects the efficacy of Islamic Education management. This indicates that the leadership style of the principal accounts for 48.2% of management effectiveness. These results suggest that a leader's style particularly transformational leadership has a significant impact on how well Islamic education initiatives are planned, carried out, coordinated, and overseen in educational institutions.